'Distance creates distance': preschool staff experiences and reflections concerning preschool introduction during the covid-19-Pandemic. Issue 1 (2nd January 2023) - Andersson Søe, Martina; Schad, Elinor; Psouni, Elia
ABSTRACT: The social restrictions during the covid-19 pandemic have challenged many aspects of preschool everyday life. Particularly vulnerable to these restrictions is the aspect of introducing new children to preschool, since preschool introduction constitutes a natural arena for establishment of preschool staff's relationships with children and their parents. Based on analysis of open-ended survey data ( N = 465), the present study explores how Swedish preschool staff has experienced and dealt with the pandemic restrictions during preschool introduction. Our qualitative analysis resulted in three categories and six subcategories, including results demonstrating that social distancing-restrictions accentuate the importance of engaging relationally with the families, while simultaneously constituting a disconcerting complication since the physical distance constrains the important relationship-building between staff and parents. Moreover, the children seem to interpret the parent-staff physical distance as relational distance, which negatively affects their emerging relationship to preschool staff. Our results also show that how parental participation is organised during preschool introduction may be of critical importance for staff-child relational establishment, providing insights for researchers and practitioners in the field valuable to consider also in a non-pandemic context.